2013
DOI: 10.1002/j.2168-0159.2013.tb06401.x
|View full text |Cite
|
Sign up to set email alerts
|

P.16: Dynamic Supply Voltage Scaling of Pixel Circuits for Static Power Reduction in AMOLEDs

Abstract: One‐dimensional (1‐D) Dynamic supply Voltage Scaling (DVS) scheme with image distortion compensation is proposed for reducing the static power consumption in AMOLED displays. A hybrid simulation platform combining MATLAB and circuit simulator HSPICE was built for the study. By applying the DVS scheme to both static images and video streams, it is shown significant power saving can be achieved (>40% for the test video streams) without sacrifice of the image or video quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Based on these results, it can be concluded that with the drain dependent near-threshold characteristics in poly-Si TFTs, more accurate control of the lower gray levels can be achieved by scaling V SS and V DATA . Scaling of V SS would also bring benefit of reducing the power loss on the driving TFTs at lower gray levels [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, it can be concluded that with the drain dependent near-threshold characteristics in poly-Si TFTs, more accurate control of the lower gray levels can be achieved by scaling V SS and V DATA . Scaling of V SS would also bring benefit of reducing the power loss on the driving TFTs at lower gray levels [8].…”
Section: Resultsmentioning
confidence: 99%
“…For that, in addition to a voltage drop on the OLED (V OLED ), a large enough drain-to-source voltage of the driving TFT (>V TFT ) is also needed to allow the device to be operated in the saturation regime. However, at lower gray levels, the OLED voltage decreases, and the voltage over the TFT is larger than what is required, causing power loss [8]. To reduce the power loss, several approaches on dynamic scaling of the supply voltage according to the displayed gray levels have been proposed [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation